Factors Influencing Stress in Spouses of Hospitalized Women Diagnosed with Preterm Labor - Jeong Im Lee; Sehoon Hong (Korean Society of Women Health Nursing, 2019)
PURPOSE: The purpose of the study was to identify to identify the nursing needs and stress levels among spouses of women hospitalized with preterm labor, and to determine factors influencing spousal stress. METHODS: Data were collected from 95 spouses of hospitalized pregnant women due to preterm labor at a hospital in Gyeonggi province from June to December of 2016. The data were analyzed by descriptive statistics, t-test, ANOVA, Pearson's correlation coefficient, and multiple linear regression. RESULTS: The mean score of spouses' nursing needs was 3.06±0.42 and stress was 1.85±0.44 out of 4.00. The highest score of nursing needs was 3.37±0.51 in assurance and the highest score for stress was 2.26±0.72 for patient's illness and prognosis. There was a significant positive correlation between stress in spouse and nursing needs (p=.004). Stress was explained by nursing needs (β=.28) and hospitalization days (β=.21). CONCLUSIONS: The results of this study suggest that appropriate nursing interventions are required to address the nursing needs at the beginning of hospitalization and to reduce the stress among spouses of hospitalized pregnant women diagnosed with preterm labor.